From Science to Action: The Role of Student Entrepreneurship in Youth Unemployment Reduction Strategy - Rahmayanti, Ifada (Economic: Journal Economic and Business, 2025)
Youth unemployment in Indonesia remains a structural challenge that impacts the nation's competitiveness. Higher education institutions are expected to be the driving force behind the transformation of graduates from job seekers to job creators. This research is part of a three-year longitudinal study aimed at analyzing the effectiveness of the Young Dahlan Entrepreneurship Program at Ahmad Dahlan University (UAD) since the end of 2024 in shaping students' entrepreneurial readiness. This first phase of research used a descriptive quantitative method with an exploratory approach to 35 respondents who also served as booth attendants. The instrument consisted of 26 questions on four dimensions of entrepreneurship, measured on a Likert scale of 1-4. Data were analyzed using SPSS to test validity, reliability, normality, and descriptive statistics (mean, median, mode). The results showed that "Entrepreneurial Spirit" was the highest dimension (mean -3.78), while "Risk Taking" was the lowest (mean = 3.54). The SWOT analysis and COWS strategy indicated the need for interventions based on business simulations and mentoring. The findings of this study led to the formation of a new theoretical framework formulated as an Asymmetric Readiness Profile. This article forms the basis for the direction of curriculum strengthening and subsequent longitudinal measurement.